а) (3а - 7в) - (4а + 8в) = 3а – 7в – 4а – 8в = (3а – 4а) + (- 7в – 8в) = - а – 15в;б) - (5m - 7n) + (2n +12m) = - 5m + 7n + 2n + 12m = (- 5m + 12m) + (7n + 2n) = 7m + 9n;в) 3x (1 - 4x) - 5x (5x + 7) = 3x * 1 + 3x * (- 4x) – 5x * 5x – 5x * 7 = 3x – 12x^2 – 25x^2 – 35x = (3x – 35x) + (- 12x^2 – 25x^2) = - 33x – 37x^2;г) 5c (2c + a) + (3c - 2a) (5a - 2c) = 5c * 2c + 5c * a + 3c * 5a + 3c * (- 2c) + (- 2a) * 5a + (- 2a) * (- 2c) = 10c^2 + 5ac + 15ac – 6c^2 – 10a^2 + 4ac = (10c^2 – 6c^2) + (5ac + 15ac + 4ac) – 10a^2 = 4c^2 + 24ac – 10a^2;д) (5y - 3)^2 - (2 - 5y)^2 = (5y)^2 – 2 * 5y * 3 + 3^2 – (2^2 – 2 * 2 * 5y + (5y)^2) = 25y^2 – 10y + 9 – (4 – 20y + 25y^2) = 25y^2 – 10y + 9 – 4 + 20y - 25y^2 = (25y^2 – 25y^2) + (- 10y + 20y) + (9 – 4) = 10y + 5.